(untitled) (Sains Humanika, 2017)
One of the criticisms on the Common European Framework of Reference (CEFR) rating scales pertains to the lack of reference to the performance of learners in the construction process of the scales. Therefore, this study attempted to delve into rating scale functioning by English as a Second Language (ESL) learners during self-assessment and peer assessment of their oral proficiency practice. Two objectives guided the study: 1) to gauge the overall rating scale functioning and 2) to measure each criterion scaling structure. Three self- and peer assessmentsâ€™ cycles were conducted in three months. In each cycle, eleven learners recorded their own speech, uploaded their video clips to a private YouTube channel and assessed their own videos as well as selected peers based on five CEFR oral assessment criteria with six levels of ratings (A1-C2). Findings revealed that four of the CEFR levels were utilised (B1-C2). Categories A1 and A2 (basic user level) however, were not observed during the practice. Analysis from the Many-Facet Rasch Measurement (MFRM) indicated that utilised categories seemed to function usefully since each category observed was advancing by more than 1.4 logits. Category B2 dominated four criteria of ratings awarded while B1 dominated the rating distribution for fluency. The implications of this study will be discussed in relation to rating scale development, specifically on matching learnersâ€™ proficiency to the psychometrically developed rating criteria as well as illustrating assessment as learning approach in the ESL classroom where learners become the key assessors for their own performance.Â